Alternative approach for establishing the Nacelle Transfer Function. Issue 4 (August 2016) - Krishna, Vinay B; Ormel, Frank; Hansen, Kurt S
The IEC 61400-12-2:2013 is an alternative for all the power performance measurements and analysis when the requirements of the IEC 61400-12-1:2005 are not met. The methodology in the IEC 61400-12-2 standard is solely based on the nacelle anemometry instead of the more traditional methods involving a met-mast, as per the IEC 61400-12-1 standard. In the IEC 61400-12-2 standard the wind speed, which is the key for all the power performance characteristics, will be measured using an anemometer mounted on or near the wind turbine's nacelle. Thus the measured wind speed in this location will be strongly affected by the wind turbine's rotor and the nacelle. Suitable correction against such flow distortion is applied through a nacelle transfer function (NTF). The -12-2 standard requires a self-consistency check performed on such established NTF using the nacelle power curve. Most of these self-consistency checks have failed to meet the criteria listed in the standard. The root cause analysis against such failure showed that the methodology followed by the standard is less accurate in estimating the free stream wind speed. Suitable changes were made in the process of establishing the nacelle transfer function and the subsequent self-consistency checks were found to be clearing the criteria set by the standard.